PENGGUNAAN HERBAL, HIPOFIBRINOGENEMIA, DAN IMPLIKASI KLINIS PERDARAHAN PADA PASIEN KARDIOVASKULAR RAWAT INAP YANG DITERAPI WARFARIN DI RSUD KABUPATEN TANGERANG: Herbal Use And Hypofibrinogenemia On Clinical Implications Of Bleeding In Warfarin-Treated Cardiovascular Patients - Muhamad Yqbal; Dian Ratih Laksmitawati; M. Iqbal Julian R.P.P; Siti Elkana Nauli (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
Bleeding complications are a significant contributor to hospitalization in cardiovascular patients on warfarin therapy; however, the contributing factors remain incompletely characterized. This study aimed to describe herbal use patterns, evaluate clinical outcomes (average length of stay/ALOS, rehospitalization, ICU transfer, and mortality), and examine bivariate associations between potential risk factors and bleeding events in hospitalized cardiovascular patients receiving warfarin at RSUD Kabupaten Tangerang. Data were analyzed using JAMOVI version 2.6.2, encompassing univariate and bivariate analyses. A total of 132 patients were included: 44 (33.3%) with bleeding and 88 (66.7%) without. The most frequently consumed herbs were garlic (28.95%), ginger (23.68%), and turmeric (21.05%). Clinically, bleeding was associated with a mean LOS of 3.70 days, rehospitalization rate of 22.7%, ICU transfer of 2.3%, and mortality of 2.3%. Chi-square analysis identified significant associations with herb use (p<0.001; OR=460), INR ≥3 (p<0.001; OR=8.33), and hypofibrinogenemia (p<0.001; OR=179). Herb use, INR ≥3 and hypofibrinogenemia have a significant association with bleeding events in cardiovascular patients undergoing warfarin therapy. Keywords: : Cardiovaskular, Clinical Outcomes, Herb Use, Hypofibrinogenemin, Warfarin